Dynamic wheeled motion control of wheel-biped transformable robots - Chao Zhang; Tangyou Liu; Shuang Song; Jiaole Wang; Max Q.-H. Meng (Biomimetic Intelligence and Robotics, 2022)
Most existing biped robots can only walk with their feet or move by wheels. To combine the best of both worlds, this paper introduces the dynamic wheeled control including wheeled locomotion and in-situ wheel-to-foot (WtF) transformation of a full-sized wheel-biped transformable robot SR600-II. It can traverse on flat surfaces by wheels and transform to footed stance through its switching modules when facing obstacles. For wheeled locomotion, the kinematics considering upper-body lumped center-of-mass (CoM) constraint is first derived. Then, the dynamics of wheeled locomotion is modeled as a wheeled inverted pendulum (WIP) with variables related to the pose of upper body. After that, a parameter-varying linear quadratic regulator (LQR) controller is utilized to enable dynamic wheeled locomotion. For WtF transformation, the WtF balance constraints are first revealed. Then, a WtF transformation strategy is proposed to tackle the problem when robot transforms from wheeled balance state to in-situ biped stance state. It enables the robot to pass by the transition stages in which both wheels and feet touch the ground and to maintain its balance at the same time. Simulations and experiments on the SR600-II prototype have validated the efficacy of proposed dynamic wheeled control strategies for both wheeled locomotion and in-situ WtF transformation.